NORMALIZATION STUDENT INFORMATION SYSTEM DATA BASE ON AMIK VETERAN PURWOKERTO - Setya Dwiko R; DR. Djoko Harmantyo. Msc (Jurnal Sistem Informasi, 1992)
By analyzing the student information system needs and pay attention to the existingobstacles so the writer, together with leaders and staff of informatics and computermanagement colleges try for mutual pour ideas for later menginplementasikan a newinformation system that facilitates the management and staff in providing services,expedite service time and increase service quality in order to provide informationservices to students with the best. Normalizing the data base student informationsystem utilizing technological advances in the field of informatics computer, here aredescribed on the use of external storage and organizing files in the application so thatthe student information system, can be utilized optimally.